Criação audiovisual na convivência dialógica em um grupo de dança de rua como processo de educação humanizadora - Ribeiro Junior, Djalma (2009)
This research was developed between 2007 and 2009 in the context of a humanizing process of audiovisual creation which values the creation and criticism ability of the young participants of Arte Urbana group, a street dance group established in Jardim Cruzeiro do Sul, in São Carlos-SP suburb. The study is conducted through the audiovisual creation process, clarifying the pedagogical contribution by the universe of images and sounds to support a proposal of popular education constructed in communion through action research and dialogue, and therefore, dialectic and intersubjective between the subjects involved in this research. It is not just about a technical knowledge proposal related to audiovisual creation, but it is essential that this technical knowledge keep up with an awareness process, a critical approach with the reality of all involved in this process. Keeping on, the audiovisual creation process contributes to construct a critical consciousness linked to the individual creation and achievement ability, enabling the development of an audiovisual work that attends the whole group interests. The research intends to contribute to the debate on educational research methodologies, proposing and experiencing an action research, ethically committed to the popular groups, constructed itself by subjects who cohabit and dialog, who are educated at the same time that educate. Using the methodology of action research, a video was created to contribute to the affirmation of the street dance as a cultural movement and to make a positive image of its participants before the society. Therefore, the main question has become to identify how potential is the audiovisual creation process to contribute to the affirmation of the street dance as a culture and to make a positive image of its participants. The answer for this question gave prominence for the educational processes present in the group and which have contributed to the creation of an audiovisual work constructed in the humanizing perspective and in the dialogue between all the ones who participated in this research action. Thus, the research aimed to understand the educational processes applied during an audiovisual creation practice constructed in a collective and dialogical way, identifying if this audiovisual creation process has collaborate to solve the problem indicated by the group. We have attended the activities, meetings, rehearsals and presentations of Arte Urbana group and the audiovisual creation was inserted into the daily life of the group. During this process we did interviews, talks and observations. After the gotten data were organized and analyzed, they brought up some important values in the group as love, trust, respect, responsibility. The participants have associated the group with a family who has the dialogue and the autonomy as two of the most remarkable characteristics. This deep experience with Arte Urbana family have showed that there are possibilities of working with audiovisual creation processes inserted in social practices, in order to assist in the human formation.